2014
DOI: 10.1097/jto.0000000000000278
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Prognostic Serum Interleukin-8 and Interleukin-6 Classifier for Stage 1 Lung Cancer in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial

Abstract: Hypothesis The advent of LDCT for lung cancer screening will likely lead to an increase in the detection of stage I lung cancer. Presently, these patients are primarily treated with surgery alone and ~ 30% will develop recurrence and die. Biomarkers that can identify patients for whom adjuvant chemotherapy would be a benefit could significantly reduce both patient morbidity and mortality. Herein, we sought to build a prognostic inflammatory-based classifier for stage I lung cancer. Methods We performed a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 55 publications
6
43
1
Order By: Relevance
“…Baseline CRP has been validated as prognostic marker in a variety of solid tumours [8], including LC [14], but the reason for such a prognostic effect is still unclear. Several mechanisms have been hypothesised to explain this association: (i) CRP is a marker of chronic inflammation that causes DNA injury and weakening of the immune system, enhancing carcinogenesis and tumour progression [23]; (ii) tumour cells and TIM may release several cytokines and chemokines, thus resulting in inflammatory cell infiltration into the cancer microenvironment and increasing the serum CRP concentrations [24]; (iii) tumour growth itself may cause inflammation of surrounding tissue [15] and (iv) the host may produce higher CRP levels as a result of immune response [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline CRP has been validated as prognostic marker in a variety of solid tumours [8], including LC [14], but the reason for such a prognostic effect is still unclear. Several mechanisms have been hypothesised to explain this association: (i) CRP is a marker of chronic inflammation that causes DNA injury and weakening of the immune system, enhancing carcinogenesis and tumour progression [23]; (ii) tumour cells and TIM may release several cytokines and chemokines, thus resulting in inflammatory cell infiltration into the cancer microenvironment and increasing the serum CRP concentrations [24]; (iii) tumour growth itself may cause inflammation of surrounding tissue [15] and (iv) the host may produce higher CRP levels as a result of immune response [25].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of circulating CRP are associated with an increased risk of LC in cancerfree individuals [9], as well as low-dose computed tomography screening participants [10], and the value of CRP in predicting disease progression and response to therapy has been widely explored in the setting of chronic inflammatory, cardiovascular and chronic obstructive pulmonary disease [11,12]. A recent metaanalysis outlined that higher baseline CRP level is associated with significantly poorer prognosis in resected LC [13], thereby suggesting that pretreatment CRP levels could be used as prognostic factors in early-stage LC, alone or in combination with other tumour or patient features [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on laboratory animals have demonstrated that increased levels of serum IL-6 and vascular endothelial growth factor are associated with tumor relapse; the strongest association has been found for adenocarcinoma [26]. IL-8 causes accumulation of neutrophils, which can directly kill cancer cells, but, on the other hand, IL-8 possesses angiogenic activity and thus contributes to formation of new blood vessels and therefore to the tumor development [27].…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that elevated levels of circulating IL-8 allow predicting lung cancer 5 years before manifestations of clinical symptoms [37]. In general, the combined assay of IL-6 and IL-8 in serum can be a useful tool for determination of tactics for treatment of patients with lung cancer [26]. Despite the numerous literature data, the dynamics of salivary IL-6 and IL-8 is not uniform: regardless of the histological type of lung cancer, the level of IL-6 is higher than that for the control group, while IL-8 is lower (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation